Perfluoroalkyl acid and bisphenol-A exposure via food sources in four First Nation communities in Quebec, Canada - Claudelle Dubeau; Amira Aker; Élyse Caron-Beaudoin; Pierre Ayotte; Caty Blanchette; Nancy Gros-Louis McHugh; Mélanie Lemire (Public Health Nutrition, 2023)
Abstract Objective: To document perfluoroalkyl acids (PFAA) and bisphenol-A (BPA) exposure in four First Nation communities in northern Quebec compared with the Canadian Health Measures Survey (CHMS Cycle 5 2016–2017) and examine the associations between dietary consumption and chemical exposure. Design: We used cross-sectional data from the JES-YEH! project conducted in collaboration with four First Nation communities in 2015. A FFQ collected information on diet, and PFAA and BPA were measured in biological samples. We used generalised linear models to test the associations between food intake and chemical biomarkers. Setting: Northern Quebec. Participants: Youth aged 3–19 years (n 198). Results: Mean perfluorononanoic acid (PFNA) levels were significantly higher in JES-YEH! than CHMS, and BPA levels were higher among those aged 12–19 years compared with CHMS. Dairy products were associated with PFNA among Anishinabe and Innu participants (geometric mean ratio 95 % CI: 1·53 (95 % CI 1·03, 2·29) and 1·52 (95 % CI 1·05, 2·20), respectively). PFNA was also associated with ultra-processed foods (1·57 (95 % CI 1·07, 2·31)) among Anishinabe, and with wild fish and berries (1·44 (95 % CI 1·07, 1·94); 1·75 (95 % CI 1·30, 2·36)) among Innu. BPA was associated with cheese (1·72 (95 % CI 1·19, 2·50)) and milk (1·53 (95 % CI 1·02, 2·29)) among Anishinabe, and with desserts (1·71 (95 % CI 1·07, 2·74)), processed meats (1·55 (95 % CI 1·00, 2·38)), wild fish (1·64 (95 % CI 1·07, 2·49)) and wild berries (2·06 (95 % CI 1·37, 3·10)) among Innu. Conclusions: These results highlight the importance of better documenting food-processing and packaging methods, particularly for dairy products, and their contribution to endocrine disruptors exposures as well as to promote minimally processed and unpackaged foods to provide healthier food environments for youth in Indigenous communities and beyond.